Paleontology and geology of Laetoli human evolution in context. Volume 1 Geology, geochronology, paleoecology and paleoenvironment - Harrison, Terry; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This volume 1 and its companion volume 2 present the results of new investigations into the geology, paleontology and paleoecology of the early hominin site of Laetoli in northern Tanzania. The site is one of the most important paleontological and paleoanthropological sites in Africa, worldrenowned for the discovery of fossils of the early hominin Australopithecus afarensis, as well as remarkable trails of its footprints. The first volume provides new evidence on the geology, geochronology, ecology, ecomorphology and taphonomy of the site. The second volume describes newly discovered fossil hominins from Laetoli, belonging to Australopithecus afarensis and Paranthropus aethiopicus, and presents detailed information on the systematics and paleobiology of the diverse associated fauna. Together, these contributions provide one of the most comprehensive accounts of a fossil hominin site, and they offer important new insights into the early stages of human evolution and its context.
1 Laetoli revisited: Renewed paleontological and geological investigations at localities on the Eyasi Plateau in northern Tanzania -- 2 Paleontological localities on the Eyasi Plateau, including Laetoli -- 3 Sedimentology, lithostratigraphy and depositional history of the Laetoli area -- 4 40Ar/39Ar dating of Laetoli, Tanzania -- 5 Petrology, geochemistry and age of Satiman, Lemagurut and Oldeani: sources of the volcanic deposits of the Laetoli area -- 6 Geochemistry and mineralogy of Laetoli area tuffs: Lower Laetolil through Naibadad Beds -- 7 Geochemical and mineralogic characterization of Middle Stone Age tools of Laetoli, Tanzania, and comparisons with possible source materials -- 8 The ecology and biogeography of the Endulen-Laetoli area in northern Tanzania -- 9 Phytoliths and pollen, the microscopic plant remains in Pliocene volcanic sediments around Laetoli, Tanzania -- 10 Fossil woods -- 11 Fossil leaves, fruits and seeds -- 12 Serengeti micromammal communities and the paleoecology of Laetoli, Tanzania -- 13 The taphonomy and paleoenvironmental implications of the Laetoli micromammals -- 14 Coprolites: Taphonomic and paleoecological implications -- 15 Stable isotopic analyses of Laetoli fossil herbivores -- 16 Feeding ecology and niche partitioning of the Laetoli ungulate faunas -- 17 Paleoenvironments of Laetoli, Tanzania as determined by antelope habitat preferences -- 18 Environmental change within the Laetoli fossiliferous sequence: vegetation catenas and bovid ecomorphology -- 19 Large mammal evidence for the paleoenvironment of the Upper Laetolil and Upper Ndolanya Beds of Laetoli, Tanzania.
Electronic reproduction.
Keywords: Geography; Geology; Paleontology; Electronic books; Laetoli Site (Tanzania).